THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN PT. PERKEBUNAN NUSANTARA IV REGIONAL II CITY OF MEDAN - Mesi Anjani; Supriadi; Syafrizal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The formulation of the problem in this study is whether there is an influence of training on employee performance, whether there is an influence of work motivation on employee performance, whether there is an influence of training and work motivation on employee performance at PT. Perkebunan Nusantara IV Regional II Medan City, this study aims to determine and analyze the influence of training on employee performance, to determine and analyze the influence of work motivation on employee performance, to determine and analyze the influence of training and work motivation on employee performance at PT. Perkebunan Nusantara IV Regional II Medan City. The methods used in this study are validity test, reliability test, classical assumption test, linear regression, and hypothesis test. Data were measured or processed using SPSS, with samples using questionnaires distributed to 40 employees at PT. Perkebunan Nusantara IV Regional II Medan City. The results of this study indicate that the training variable has a positive and significant effect on employee performance. The work motivation variable has a positive and significant effect on employee performance. The training and work motivation variables have a positive and significant effect on employee performance. Keywords: Training, Work Motivation, Employee Performance.